Polycarboxylate superplasticizer containing nano material and preparation method thereof
By introducing nanomaterials, especially alkenyl modified silane chitosan, the existing water reducers in terms of concrete durability and compressive strength, and better performance improvements have been achieved.
Patent Information
- Application Number
- CN202411867929.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-18
- Publication Date
- 2025-03-14
- Estimated Expiration
- 2044-12-18
AI Technical Summary
The existing polycarboxylic acid water reducing agents still have room for improvement in improving concrete performance, especially in terms of durability and compressive strength.
A polycarboxylic acid water reducing agent containing nanomaterials is used to form a water reducing agent with improved properties by adding nanomaterials such as alkenyl modified silane chitosan during its preparation process.
It significantly improves the durability and compressive strength of concrete, reduces the chloride ion diffusion coefficient, and reduces the adsorption of clay to polycarboxylic acid water reducing agent, thereby ensuring good performance of concrete.
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of concrete admixtures, in particular to a polycarboxylate water reducer containing nano materials and a preparation method thereof. Background Art
[0002] Concrete is an artificial stone made of gel material, aggregate, water and admixture in a certain proportion. It has the characteristics of abundant raw materials, low price and simple production process. However, in the process of use, some admixtures need to be added to meet the performance requirements.
[0003] For example, patent CN107189021A discloses a polycarboxylic acid water reducer and a preparation method thereof. The invention can avoid the problem of low efficiency caused by using a reducing agent at a lower temperature, and can shorten the dripping time, shorten the production cycle, reduce energy consumption, and reduce production costs; however, its performance needs to be improved. Summary of the invention
[0004] 1. Technical issues to be resolved In view of the deficiencies in the prior art, the present invention provides a polycarboxylate water-reducing agent containing nanomaterials and a preparation method thereof, which improves the durability and compressive strength of concrete.
[0005] (II) Technical solution To achieve the above object, the present invention provides the following technical scheme: a polycarboxylate water-reducing agent containing nanomaterials, comprising the following components by weight: 5-9 parts by weight of alkenyl-modified silane chitosan, 150-220 parts by weight of isopentanol polyoxyethylene ether, 35-60 parts by weight of methyl acrylate, 40-70 parts by weight of diethylene glycol monoacrylate, 5-8 parts by weight of ammonium chloride, 3-4 parts by weight of ferrous sulfate, 1-2 parts by weight of mercaptoethanol reducing agent, 0.8-1.3 parts by weight of thioglycolic acid chain transfer agent, 2-3 parts by weight of sodium persulfate initiator, and 80-100 parts by weight of water.
[0006] Preferably, the preparation method of the alkenyl-modified silane chitosan is: (1) Allyl glycidyl ether, tetrahydrofuran solvent and chloroplatinic acid are added to a reactor, activated at 45-60°C for 30-50 minutes, and then 1,1,3,3-tetramethyldisiloxane is added dropwise for 50-65 minutes. The reaction is continued at 55-65°C for 4-7 hours. After the reaction is completed, the mixture is cooled to room temperature, an activated carbon adsorbent is added, ultrasonically shaken for 30-40 minutes, the catalyst chloroplatinic acid is removed, filtered, and rotary evaporated to obtain epoxy-modified siloxane; (2) adding 6-10 parts by weight of chitosan to dimethyl sulfoxide solvent to dissolve, stirring evenly, adding 5-8 parts by weight of 2,3-epoxypropyltrimethylammonium chloride at constant pressure, reacting at 70-90° C., washing with anhydrous ethanol after the reaction, drying, dialyzing, and concentrating to obtain quaternized chitosan; (3) adding 6-10 parts by weight of quaternized chitosan to the acetic acid solution, stirring evenly, and then adding 10-16 parts by weight of epoxy-modified siloxane thereto, ultrasonically shaking at 50-60° C., cooling to room temperature, adding hydrochloric acid dropwise until neutral, washing and drying to obtain modified chitosan; (4) Add 4-7 parts by weight of modified chitosan and 6-15 parts by weight of acrylic acid to N,N-dimethylformamide solvent, stir evenly, then add 0.2-0.3 parts by weight of p-toluenesulfonic acid catalyst, react for 10-13 hours, and then perform vacuum distillation, filter and dry to obtain alkenyl-modified silane chitosan.
[0007] Preferably, the mass ratio of allyl glycidyl ether, chloroplatinic acid and 1,1,3,3-tetramethyldisiloxane in (1) is 1:0.01-0.03:1.1-1.2.
[0008] Preferably, the reaction time in (2) is 6-8 hours.
[0009] Preferably, the ultrasonic oscillation time in (3) is 30-40 minutes.
[0010] Preferably, the reaction temperature in (4) is 85-110°C.
[0011] Preferably, the preparation method of the polycarboxylate water-reducing agent containing nanomaterials is: S1. Dissolve isopentanol polyoxyethylene ether in deionized water and stir to obtain solution A; S2. Methyl acrylate and diethylene glycol monoacrylate were dissolved in deionized water and stirred to obtain a solution B; S3. The mercaptoethanol reducing agent, the thioglycolic acid chain transfer agent and the sodium persulfate initiator were dissolved in deionized water, and stirred to obtain solutions C, D and E, respectively; S4. Add solution A, alkenyl-modified silane chitosan, water, ammonium chloride, and ferrous sulfate into the reactor, and add sodium persulfate initiator solution E, mercaptoethanol reducing agent solution C, and thioglycolic acid chain transfer agent solution D under stirring conditions to initiate a polymerization reaction, and then drop solution B therein; after the dropwise addition is completed, react at 40-60°C for 2-6h, cool the product to room temperature, and then adjust the pH value to neutral with alkali solution to obtain a polycarboxylic acid water reducer containing nanomaterials.
[0012] 3. Beneficial technical effects The invention comprises the following steps: adding solution A, alkenyl-modified silane chitosan, water, ammonium chloride and ferrous sulfate into a reactor, and adding a sodium persulfate initiator solution E, a mercaptoethanol reducing agent solution C and a thioglycolic acid chain transfer agent solution D under stirring conditions to initiate a polymerization reaction, and then dripping solution B therein; after the dripping is completed, reacting, cooling the product to room temperature, and then adjusting the pH value to neutral with an alkali solution to obtain a polycarboxylate water reducer containing nano materials.
[0013] The chitosan in the alkenyl-modified silane chitosan can reduce the diffusion coefficient of chloride ions, improve the impermeability and density of concrete, and also improve the durability of concrete; the siloxane group therein also improves the durability of concrete; the quaternary ammonium salt group can react with the negative charge in the clay to form a protective film to prevent water molecules and water reducer molecules from entering the interior of the clay. This effect can effectively reduce the adsorption of clay on polycarboxylic acid water reducer, thereby reducing the dosage of polycarboxylic acid admixture and ensuring good performance of concrete. DETAILED DESCRIPTION
[0014] Example 1 A polycarboxylate water-reducing agent containing nanomaterials comprises the following components by weight: 5 parts by weight of alkenyl-modified silane chitosan, 150 parts by weight of isopentanol polyoxyethylene ether, 35 parts by weight of methyl acrylate, 40 parts by weight of diethylene glycol monoacrylate, 5 parts by weight of ammonium chloride, 3 parts by weight of ferrous sulfate, 1 part by weight of mercaptoethanol reducing agent, 0.8 parts by weight of thioglycolic acid chain transfer agent, 2 parts by weight of sodium persulfate initiator and 80 parts by weight of water.
[0015] The preparation method of the alkenyl-modified silane chitosan is: (1) Allyl glycidyl ether, tetrahydrofuran solvent and chloroplatinic acid are added to a reactor, activated at 45°C for 30 minutes, and then 1,1,3,3-tetramethyldisiloxane is added dropwise, wherein the mass ratio of allyl glycidyl ether, chloroplatinic acid and 1,1,3,3-tetramethyldisiloxane is 1:0.01:1.1, and the addition time is 50 minutes. The reaction is continued at 55°C for 4 hours. After the reaction is completed, the reaction is cooled to room temperature, an activated carbon adsorbent is added, ultrasonically shaken for 30 minutes, the catalyst chloroplatinic acid is removed, filtered, and rotary evaporated to obtain epoxy-modified siloxane; (2) adding 6 parts by weight of chitosan to dimethyl sulfoxide solvent to dissolve it, stirring it evenly, adding 5 parts by weight of 2,3-epoxypropyltrimethylammonium chloride at constant pressure, reacting it at 70° C. for 6 hours, washing it with anhydrous ethanol after the reaction, drying it, dialyzing it, and concentrating it to obtain quaternized chitosan; (3) adding 6 parts by weight of quaternized chitosan to the acetic acid solution, stirring evenly, and then adding 10 parts by weight of epoxy-modified siloxane thereto, ultrasonically shaking at 50° C. for 30 min, cooling to room temperature, adding hydrochloric acid dropwise until neutral, washing and drying to obtain modified chitosan; (4) 4 parts by weight of modified chitosan and 6 parts by weight of acrylic acid were added to N,N-dimethylformamide solvent and stirred evenly. Then, 0.2 parts by weight of p-toluenesulfonic acid catalyst was added thereto. The reaction was carried out at 85° C. for 10 h. After the reaction was completed, the reaction was carried out by vacuum distillation, filtration and drying to obtain alkenyl-modified silane chitosan.
[0016] The preparation method of the polycarboxylate water-reducing agent containing nano materials is as follows: S1. Dissolve isopentanol polyoxyethylene ether in deionized water and stir to obtain solution A; S2. Methyl acrylate and diethylene glycol monoacrylate were dissolved in deionized water and stirred to obtain a solution B; S3. The mercaptoethanol reducing agent, the thioglycolic acid chain transfer agent and the sodium persulfate initiator were dissolved in deionized water, and stirred to obtain solutions C, D and E, respectively; S4. Add solution A, alkenyl-modified silane chitosan, water, ammonium chloride, and ferrous sulfate into the reactor, and add sodium persulfate initiator solution E, mercaptoethanol reducing agent solution C, and thioglycolic acid chain transfer agent solution D under stirring conditions to initiate a polymerization reaction, and then drop solution B therein; after the dropwise addition is completed, react at 40°C for 2h, cool the product to room temperature, and then adjust the pH value to neutral with alkaline solution to obtain a polycarboxylic acid water reducer containing nanomaterials.
[0017] Example 2 A polycarboxylate water-reducing agent containing nanomaterials comprises the following components by weight: 9 parts by weight of alkenyl-modified silane chitosan, 220 parts by weight of isopentanol polyoxyethylene ether, 60 parts by weight of methyl acrylate, 70 parts by weight of diethylene glycol monoacrylate, 8 parts by weight of ammonium chloride, 4 parts by weight of ferrous sulfate, 2 parts by weight of mercaptoethanol reducing agent, 1.3 parts by weight of thioglycolic acid chain transfer agent, 3 parts by weight of sodium persulfate initiator and 100 parts by weight of water.
[0018] The preparation method of the alkenyl-modified silane chitosan is: (1) Allyl glycidyl ether, tetrahydrofuran solvent and chloroplatinic acid are added to a reactor, activated at 60°C for 50 minutes, and then 1,1,3,3-tetramethyldisiloxane is added dropwise, wherein the mass ratio of allyl glycidyl ether, chloroplatinic acid and 1,1,3,3-tetramethyldisiloxane is 1:0.03:1.2, and the addition time is 65 minutes. The reaction is continued at 65°C for 7 hours. After the reaction is completed, the reaction is cooled to room temperature, an activated carbon adsorbent is added, ultrasonic vibration is performed for 40 minutes, the catalyst chloroplatinic acid is removed, and the reaction is filtered and rotary evaporated to obtain epoxy-modified siloxane; (2) adding 10 parts by weight of chitosan to dimethyl sulfoxide solvent to dissolve it, stirring it evenly, adding 8 parts by weight of 2,3-epoxypropyltrimethylammonium chloride at a constant pressure, reacting it at 90° C. for 8 hours, washing it with anhydrous ethanol after the reaction, drying it, dialyzing it, and concentrating it to obtain quaternized chitosan; (3) adding 10 parts by weight of quaternized chitosan to the acetic acid solution, stirring evenly, and then adding 16 parts by weight of epoxy-modified siloxane thereto, ultrasonically shaking at 60° C. for 40 min, cooling to room temperature, adding hydrochloric acid dropwise until neutral, washing and drying to obtain modified chitosan; (4) 7 parts by weight of modified chitosan and 15 parts by weight of acrylic acid were added to N,N-dimethylformamide solvent and stirred evenly. Then, 0.3 parts by weight of p-toluenesulfonic acid catalyst was added thereto. The reaction was carried out at 110° C. for 13 h. After the reaction, the reaction was carried out under reduced pressure distillation, filtered and dried to obtain alkenyl-modified silane chitosan.
[0019] The preparation method of the polycarboxylate water-reducing agent containing nano materials is as follows: S1. Dissolve isopentanol polyoxyethylene ether in deionized water and stir to obtain solution A; S2. Methyl acrylate and diethylene glycol monoacrylate were dissolved in deionized water and stirred to obtain a solution B; S3. The mercaptoethanol reducing agent, the thioglycolic acid chain transfer agent and the sodium persulfate initiator were dissolved in deionized water, and stirred to obtain solutions C, D and E, respectively; S4. Add solution A, alkenyl-modified silane chitosan, water, ammonium chloride, and ferrous sulfate into the reactor, and add sodium persulfate initiator solution E, mercaptoethanol reducing agent solution C, and thioglycolic acid chain transfer agent solution D under stirring conditions to initiate a polymerization reaction, and then drop solution B therein; after the dropwise addition is completed, react at 60°C for 6h, cool the product to room temperature, and then adjust the pH value to neutral with alkaline solution to obtain a polycarboxylic acid water reducer containing nanomaterials.
[0020] Example 3 A polycarboxylate water-reducing agent containing nanomaterials comprises the following components by weight: 8 parts by weight of alkenyl-modified silane chitosan, 200 parts by weight of isopentanol polyoxyethylene ether, 55 parts by weight of methyl acrylate, 60 parts by weight of diethylene glycol monoacrylate, 7 parts by weight of ammonium chloride, 3 parts by weight of ferrous sulfate, 1 part by weight of mercaptoethanol reducing agent, 0.9 parts by weight of thioglycolic acid chain transfer agent, 2 parts by weight of sodium persulfate initiator and 90 parts by weight of water.
[0021] The preparation method of the alkenyl-modified silane chitosan is: (1) Allyl glycidyl ether, tetrahydrofuran solvent and chloroplatinic acid are added to a reactor, activated at 55°C for 40 minutes, and then 1,1,3,3-tetramethyldisiloxane is added dropwise, wherein the mass ratio of allyl glycidyl ether, chloroplatinic acid and 1,1,3,3-tetramethyldisiloxane is 1:0.02:1.1, and the addition time is 55 minutes. The reaction is continued at 60°C for 6 hours. After the reaction is completed, it is cooled to room temperature, an activated carbon adsorbent is added, ultrasonically shaken for 35 minutes, the catalyst chloroplatinic acid is removed, filtered, and rotary evaporated to obtain epoxy-modified siloxane; (2) adding 8 parts by weight of chitosan to dimethyl sulfoxide solvent to dissolve it, stirring it evenly, adding 6 parts by weight of 2,3-epoxypropyltrimethylammonium chloride at a constant pressure, reacting it at 80° C. for 7 hours, washing it with anhydrous ethanol after the reaction, drying it, dialyzing it, and concentrating it to obtain quaternized chitosan; (3) adding 8 parts by weight of quaternized chitosan to the acetic acid solution, stirring evenly, and then adding 13 parts by weight of epoxy-modified siloxane thereto, ultrasonically shaking at 55° C. for 35 min, cooling to room temperature, adding hydrochloric acid dropwise until neutral, washing and drying to obtain modified chitosan; (4) Add 6 parts by weight of modified chitosan and 8 parts by weight of acrylic acid into N,N-dimethylformamide solvent and stir evenly. Then add 0.2 parts by weight of p-toluenesulfonic acid catalyst and react at 100° C. for 12 h. After reaction, perform vacuum distillation, filter and dry to obtain alkenyl-modified silane chitosan.
[0022] The preparation method of the polycarboxylate water-reducing agent containing nano materials is as follows: S1. Dissolve isopentanol polyoxyethylene ether in deionized water and stir to obtain solution A; S2. Methyl acrylate and diethylene glycol monoacrylate were dissolved in deionized water and stirred to obtain a solution B; S3. The mercaptoethanol reducing agent, the thioglycolic acid chain transfer agent and the sodium persulfate initiator were dissolved in deionized water, and stirred to obtain solutions C, D and E, respectively; S4. Add solution A, alkenyl-modified silane chitosan, water, ammonium chloride, and ferrous sulfate into the reactor, and add sodium persulfate initiator solution E, mercaptoethanol reducing agent solution C, and thioglycolic acid chain transfer agent solution D under stirring conditions to initiate a polymerization reaction, and then drop solution B therein; after the dropwise addition is completed, react at 50°C for 4h, cool the product to room temperature, and then adjust the pH value to neutral with alkaline solution to obtain a polycarboxylic acid water reducer containing nanomaterials.
[0023] Comparative Example 1 Compared with Example 3, this comparative example is different in that no alkenyl-modified silane chitosan is added.
[0024] Performance Testing At 20-35°C, medium sand and gravel are poured into a mixer and stirred for 1-2 minutes, fly ash and cement are added thereto and stirred continuously for 5-8 minutes, polycarboxylate water-reducing agent containing nano materials is poured into water and stirred evenly, water is slowly added to the stirred mixture, and stirring is continued for 3-5 minutes. After the mixture is finished, it is cast into a mold, cured at room temperature for 20-24 hours, formed and demolded, and then cured in a standard curing room for 30-35 days to obtain a 150mm*150mm*150mm concrete specimen; wherein the mass ratio of medium sand, gravel, fly ash, cement, water, and polycarboxylate water-reducing agent containing nano materials is 1.2-1.4:2.3-2.8:0.5-0.6:1:0.4-0.6:0.04-0.06.
[0025] The concrete specimens prepared in Example 13 and Comparative Example 1 were tested for compressive strength, flexural strength and chloride ion diffusion coefficient, wherein the compressive strength and flexural strength tests were conducted in accordance with GB / T 500812002 "Standard for Test Methods of Mechanical Properties of Ordinary Concrete", and the chloride ion diffusion coefficient test was conducted in accordance with GB / T 500822009 "Standard for Test Methods of Long-term Performance and Durability of Ordinary Concrete". The specific test results are shown in Table 1. In addition, according to GB / T504762008 "Concrete Structure Durability Design Code", the chloride ion diffusion coefficient of Class E structure with a design life of 100 years should be less than 4×10 12 m 2 / s.
[0026] Table 1: Performance tests.
[0027]
[0028] It can be seen from Table 1 that Examples 1-3 of the present invention have better compressive strength and flexural strength than Comparative Example 1, and also have better resistance to chloride ion corrosion.
[0029] The preferred embodiments of the present invention disclosed above are only used to help illustrate the present invention. The preferred embodiments do not describe all the details in detail, nor do they limit the invention to the specific implementation methods described. Obviously, many modifications and changes can be made according to the content of this specification. This specification selects and specifically describes these embodiments in order to better explain the principles and practical applications of the present invention, so that those skilled in the art can understand and use the present invention well. The present invention is limited only by the claims and their full scope and equivalents.
Claims
1. A polycarboxylate water-reducing agent containing nanomaterials, characterized in that: The invention comprises the following components by weight: 5-9 parts by weight of alkenyl modified silane chitosan, 150-220 parts by weight of isopentanol polyoxyethylene ether, 35-60 parts by weight of methyl acrylate, 40-70 parts by weight of diethylene glycol monoacrylate, 5-8 parts by weight of ammonium chloride, 3-4 parts by weight of ferrous sulfate, 1-2 parts by weight of mercaptoethanol reducing agent, 0.8-1.3 parts by weight of thioglycolic acid chain transfer agent, 2-3 parts by weight of sodium persulfate initiator and 80-100 parts by weight of water.
2. The polycarboxylate water-reducing agent containing nanomaterials according to claim 1, characterized in that: The preparation method of the alkenyl-modified silane chitosan is: (1) Allyl glycidyl ether, tetrahydrofuran solvent and chloroplatinic acid are added to a reactor, activated at 45-60°C for 30-50 minutes, and then 1,1,3,3-tetramethyldisiloxane is added dropwise for 50-65 minutes. The reaction is continued at 55-65°C for 4-7 hours. After the reaction is completed, the mixture is cooled to room temperature, an activated carbon adsorbent is added, ultrasonically shaken for 30-40 minutes, the catalyst chloroplatinic acid is removed, filtered, and rotary evaporated to obtain epoxy-modified siloxane; (2) adding 6-10 parts by weight of chitosan to dimethyl sulfoxide solvent to dissolve, stirring evenly, adding 5-8 parts by weight of 2,3-epoxypropyltrimethylammonium chloride at constant pressure, reacting at 70-90° C., washing with anhydrous ethanol after the reaction, drying, dialyzing, and concentrating to obtain quaternized chitosan; (3) adding 6-10 parts by weight of quaternized chitosan to the acetic acid solution, stirring evenly, and then adding 10-16 parts by weight of epoxy-modified siloxane thereto, ultrasonically shaking at 50-60° C., cooling to room temperature, adding hydrochloric acid dropwise until neutral, washing and drying to obtain modified chitosan; (4) Add 4-7 parts by weight of modified chitosan and 6-15 parts by weight of acrylic acid to N,N-dimethylformamide solvent, stir evenly, then add 0.2-0.3 parts by weight of p-toluenesulfonic acid catalyst, react for 10-13 hours, and then perform vacuum distillation, filter and dry to obtain alkenyl-modified silane chitosan.
3. The polycarboxylate water-reducing agent containing nanomaterials according to claim 2, characterized in that: The mass ratio of allyl glycidyl ether, chloroplatinic acid and 1,1,3,3-tetramethyldisiloxane in (1) is 1:0.01-0.03:1.1-1.
2.
4. The polycarboxylate water-reducing agent containing nanomaterials according to claim 2, characterized in that: The reaction time in (2) is 6-8h.
5. The polycarboxylate water-reducing agent containing nanomaterials according to claim 2, characterized in that: The ultrasonic oscillation time in (3) is 30-40 minutes.
6. The polycarboxylate water-reducing agent containing nanomaterials according to claim 2, characterized in that: The reaction temperature in (4) is 85-110°C.
7. A method for preparing a polycarboxylate water-reducing agent containing nanomaterials according to any one of claims 1 to 6, characterized in that: The preparation method of the polycarboxylate water-reducing agent containing nano materials is as follows: S1. Dissolve isopentanol polyoxyethylene ether in deionized water and stir to obtain solution A; S2. Dissolve methyl acrylate and diethylene glycol monoacrylate in deionized water and stir to obtain solution B; S3. The mercaptoethanol reducing agent, the thioglycolic acid chain transfer agent and the sodium persulfate initiator were dissolved in deionized water and stirred to obtain solutions C, D and E, respectively; S4. Add solution A, alkenyl-modified silane chitosan, water, ammonium chloride, and ferrous sulfate into the reactor, and add sodium persulfate initiator solution E, mercaptoethanol reducing agent solution C, and thioglycolic acid chain transfer agent solution D under stirring conditions to initiate a polymerization reaction, and then drop solution B therein; after the dropwise addition is completed, react at 40-60°C for 2-6h, cool the product to room temperature, and then adjust the pH value to neutral with alkali solution to obtain a polycarboxylic acid water reducer containing nanomaterials.
Citation Information
Patent Citations
Polycarboxylate superplasticizer and preparation method thereof
CN107189021A
Composite early-strength polycarboxylate superplasticizer and preparation method thereof
CN116535134A
Environment-friendly energy-saving water reducing agent and preparation process thereof
CN117402303A
Additive for hydraulic composition
JP1999001355A